Contemporary management of stent thrombosis: Predictors of mortality and the role of new‐generation drug‐eluting stents. Issue 1 (9th September 2019) - Katsikis, Athanasios; Keeble, Thomas R.; Davies, John R.; Jagathesan, Rohan; Kabir, Alamgir; Sayer, Jeremy W.; Robinson, Nicholas M.; Kalogeropoulos, Andreas S.; Aggarwal, Rajesh K.; Gamma, Reto A.; Tang, Kare H.; Kassimis, George; et al.
Abstract: Objectives: We sought to evaluate mortality predictors and the role of new‐generation drug‐eluting stents (NG‐DES) in stent thrombosis (ST) management. Background: No data are available regarding the outcome of patients with ST after interventional management that includes exclusively NG‐DES. Methods: Patients with definite ST of DES or BMS who underwent urgent/emergent angiography between 2015 and 2018 at our institution were considered for the study. After excluding patients who achieved TIMI‐flow<2 after intervention or received an old‐generation stent, 131 patients were included. Management classification was stent or non‐stent treatment (medical management, thromboaspiration, balloon‐angioplasty). Follow‐up was performed to document all‐cause death (ACD) and target‐lesion‐revascularization (TLR) that was used for censorship. Results: Mode of presentation was STEMI in 88% and UA/NSTEMI in 12%. Type of ST was early, late, and very late in 11, 4, and 85%, respectively. Eighty four patients received stent and 47 non‐stent treatment. After 926 ± 34 days, 21 ACDs, 7 TLRs and no cases of definite, recurrent ST were observed. Univariate predictors of in‐hospital mortality were LVEF and presentation with shock or cardiac arrest. For patients discharged alive, non‐stent treatment (HR 4.2, p = .01), TIMI‐2 flow (HR 7.4, p = .002) and GFR < 60 mL/min (HR 3.8, p = .01) were independent predictors of ACD. The stent‐treatment group had significantly better ACD‐free survival after discharge, both unadjusted ( p = .022) and adjusted ( p = .018). Conclusions: After ST management, different predictors were observed for in‐hospital mortality and mortality in patients discharged alive. The better outcome with NG‐DES treatment is a novel observation, warranting further studies to elucidate if it is associated with stent‐related or patient‐related factors.